Performance Evaluation of Shovel Type Furrow Opener of a Seed cum Fertilizer Drill in Sandy Soils - Darmora, D P; Pandey, K P (Journal of Agricultural Engineering, 2006)
A shovel type furrow opener having optimized values of rake angle, wedge angle, boot geometry and the seed-fertilizer tube spacing was evaluated against standard shovel type furrow opener (BIS) under controlled soil bin condition in sandy loam and loamy sand soils. The performance evaluation was made on the basis of draft requirement, soil cover, lateral and vertical seed scatter, lateral and vertical separations maintained between the seed and fertilizer placements and row roughness coefficient at a soil moisture of 10 per cent (db) and an operating depth and speed of 60 mm and 0.562 ms?Â¹ respectively. The furrow openers require about 18 per cent less draft and created less soil disturbance in comparison to standard shovel type furrow opener. The seed-fertilizer distribution ability of the furrow opener was also found better than the standard-shovel type furrow opener as it placed the seed and fertilizer at a lateral and vertical separations of about 33 mm and 21 mm, respectively against a negligible vertical separation maintained by the BIS-shovel type furrow opener. The value of overall performance index of the furrow opener was also much higher than the standard -shovel type furrow opener.